Locomotor Muscle Fatigue Does Not Alter Oxygen Uptake Kinetics during High-Intensity Exercise - Hopker, James G.; Caporaso, Giuseppe; Azzalin, Andrea; Carpenter, Roger; Marcora, Samuele M. (Frontiers in Physiology, 2016)
The slow component (VO2sc) that develops during high-intensity aerobic exercise is thought to be strongly associated with locomotor muscle fatigue. We sought to experimentally test this hypothesis by pre-fatiguing the locomotor muscles used during subsequent high-intensity cycling exercise. Over two separate visits, eight healthy male participants were asked to either perform a non-metabolically stressful 100 intermittent drop-jumps protocol (pre fatigue condition) or rest for 33 minutes (control condition) according to a random and counterbalanced order. Locomotor muscle fatigue was quantified with 6-second maximal sprints at a fixed pedaling cadence of 90 rev·min-1. Oxygen kinetics and other responses (heart rate, capillary blood lactate concentration and rating of perceived exertion, RPE) were measured during two subsequent bouts of 6 min cycling exercise at 50% of the delta between the lactate threshold and VO2max determined during a preliminary incremental exercise test. All tests were performed on the same cycle ergometer. Despite significant locomotor muscle fatigue (P = 0.03), the VO2sc was not significantly different between the pre fatigue (464 ± 301 mL·min-1) and the control (556 ± 223 mL·min-1) condition (P = 0.50). Blood lactate response was not significantly different between conditions (P = 0.48) but RPE was significantly higher following the pre-fatiguing exercise protocol compared with the control condition (P < 0.01) suggesting higher muscle recruitment. These results demonstrate experimentally that locomotor muscle fatigue does not significantly alter the VO2 kinetic response to high intensity aerobic exercise, and challenge the hypothesis that the VO2sc is strongly associated with locomotor muscle fatigue.